Impact of Blood Transfusion in Free Flap Breast Reconstruction Using Propensity Score Matching - Karamanos, Efstathios; Shah, Amita R.; Kim, Julie N.; Wang, Howard T. (Journal of Reconstructive Microsurgery, 2020)
Background Microvascular thrombosis has been associated with cytokine release and inflammatory syndromes which can occur as a result of blood transfusions. This phenomenon could potentially lead to complications in breast free flap reconstruction. The aim of this study was to evaluate the impact of perioperative blood transfusion in free flap breast reconstruction using large population analysis.Methods The American College of Surgeons National Quality Improvement Program database was queried for delayed free flap breast reconstructions performed in 2016. The study population was divided based on perioperative blood transfusion within 24 hours of the start of the operation. Propensity score matching analysis was used to ensure homogeneity between the two study groups. Primary outcome was unplanned return to the operating room (OR) within 30 days. Secondary outcomes were readmission and complications.Results A total of 1,256 patients were identified. Out of those, 91 patients received a perioperative blood transfusion. All the patients received only one unit of PRBC within the first 24 hours. Those patients were matched with similar patients who did not receive a transfusion on a ratio of 1:3 (273 patients). Patients who received a transfusion had a significantly higher incidence of reoperation (42 vs. 10%, p < 0.001). Patients who received a transfusion were more likely to return to the OR after 48 hours from the initial operation (13 vs. 5%, p = 0.001). All returns to the OR were due to flap-related complications. Perioperative blood transfusion increased the incidence of wound dehiscence (9 vs. 2%, p = 0.041) but had no protective effect on the development of other postoperative complications.Conclusion Perioperative blood transfusion in free flap breast reconstruction is associated with an increased probability of flap-related complications and subsequent return to the OR without decreasing the probability of developing other systemic postoperative complications.
Keywords: free flap; breast reconstruction; blood transfusion; outcomes; wound; complications